?PERFORMANCES OF NEWLY DEVELOPED COTTON STRAINS FOR ECONOMIC AND FIBRE TRAITS IN NATIONAL COORDINATED VARIETAL TRIALS (Biological Sciences - PJSIR, 2003)
To find out the responses of new cotton, strains were conducted at Central Cotton Research Institute, Multan along with a commercial variety NIAB - 78. The highest seed cotton yield was noted in CIM - 443 followed by CIM - 435. The longest staple length was noted in strain CIM - 435 followed by CIM - 443. The strain CIM - 443 was significantly better in ginning outturn percentage and number of bolls/plant followed by CIM - 435. The boll weight was the highest in CIM - 435. The newly developed strain CIM - 443 showed the best characteristics, among all the tested strains.